COVID-19 and Mental Health Consequences: The Way Forward - Giasuddin, Noor Ahmed (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
On 31 December 2019, the WHO China Country Office was informed of cases of pneumonia of unknown etiology detected in Wuhan City in Hubei Province of its territory. The Chinese authorities isolated a new type of coronavirus on 7 January 2020. The consequences of this viral infection were later termed as COVID-19 disease. Direct and indirect psychological and social effects can affect mental health now and in future. COVID-19 can infect brain and can affect brain function. During and after this pandemic, harmful behaviors like suicide and self-harm are likely to increase. SARS (2003) had 30% increase in suicide in those over 65 years. Half of the recovered patients remained anxious; 29% health care workers experienced emotional distress. When a person becomes infected with COVID-19 disease, s/he is also at higher risk for sleep problems owing to acute stress responses. Anxiety and depressive symptoms constitute common reactions for people with COVID-19 diagnosis, especially for those who may be hospitalized, due to concerns for one’s own health or the health of others, the need for physical isolation. Other concerns include the potential risk of death, concerns over the risk of infecting others, and concerns over leaving family members alone who may need care. Stress-related psychiatric conditions including mood and substance use disorders which are associated with suicidal behavior. COVID-19 survivors may also be at elevated suicide risk during and after the pandemic. The suicidal behaviors are likely to be present for a long time and peak later than the actual pandemic. Lifestyle during the pandemic is characterized by prolonged inactivity, increased eating and consequent obesity, alcohol and other substance abuse. All of these behavioral characteristics are included in maladaptive coping strategies. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(1):01-03